Good's syndrome (immunodeficiency with thymoma): A separate entity with a broad classification: Report of six cases and review of the literature. Issue 6 (17th June 2021) - Nabavi, Mohammad; Rezaeifar, Afshin; Fallahpour, Morteza; Arshi, Saba; Bemanian, Mohammad Hassan; Shokri, Sima; Atashrazm, Fatemeh; Bahrami, Sima; Asadi Gharabaghi, Mehrnaz; Rezaeifar, Parisa; Vakilazad, Zahra
Abstract: Good's syndrome is a rare adult‐onset thymoma‐associated immunodeficiency with unknown pathogenesis. Therefore, it should be carefully managed as soon as possible when complications are presented. Because of variety of immunodeficiency, this syndrome is now classified as a separate entity with a broad classification (immunodeficiency with thymoma). Abstract : Good's syndrome is a rare adult‐onset thymoma‐associated immunodeficiency with unknown pathogenesis. Therefore, it should be carefully managed as soon as possible when complications are presented. Because of variety of immunodeficiency, this syndrome is now classified as a separate entity with a broad classification (immunodeficiency with thymoma).